The impact of project-based learning on 21st century skill development of vocational engineering students: A systematic literature review - Alief Depa Rozan; Budi Syahri; Febri Prasetya; Aprilla Fortuna; Agariadne Dwinggo Samala; Soha Rawas (Researcher and Lecturer Society, 2024)
This study conducts a systematic literature review to evaluate the impact of Project-based Learning (PjBL) to vocational education and its effects on developing 21st-century skills. Utilizing the PRISMA framework, the study analyzes 21 articles from an initial pool of 1,036 papers from Scopus and Google Scholar databases. The included literature consists of articles published within the last five years (2019-2024) and systematically examines the findings from relevant studies. The analysis results demonstrate that PjBL is crucial in preparing students for a dynamic, technology-driven workforce by enhancing skills such as learning and innovation, information, media, technology, and life and career skills. Despite challenges in implementing PjBL, such as insufficient technological proficiency, inadequate resources, and misaligned curricula, PjBL offers opportunities to develop more effective pedagogical approaches aligned with industry needs. The study emphasizes the importance of collaboration between educators, policymakers, and industry stakeholders to address these challenges and improve vocational education quality. Additionally, the study identifies the need for further research to bridge existing gaps, particularly in developing information, media, and technology skills. Therefore, PjBL is a potential method for equipping students with essential skills for the ever-evolving job market.